Which Narrative Strategies Durably Reduce Prejudice? Evidence from Field and Survey Experiments Supporting the Efficacy of Perspective‐Getting. Issue 1 (31st October 2021) - Kalla, Joshua L.; Broockman, David E.
Abstract: Exclusionary attitudes towards outgroups contribute to social and political challenges worldwide. Previous field experiments found that interpersonal conversations employing multiple narrative strategies can durably reduce exclusionary attitudes. We theoretically distinguish between three of these narrative strategies: narratives which promote analogic perspective taking, vicarious perspective‐giving, and perspective‐getting. Previous research has assigned these strategies together in a compound treatment, leaving open important theoretical and practical questions about each's effectiveness. We present results from three field studies and a survey experiment that individually manipulate their presence. Across the field studies, we find omitting prompts to engage in analogic perspective‐taking and vicarious perspective‐giving does not diminish effects; conversations employing only perspective‐getting narratives durably reduce exclusionary attitudes. Results from within‐subject analyses and a survey experiment similarly show that perspective‐getting consistently reduces exclusionary attitudes and activates multiple mechanisms. These results refine theoretical understandings of prejudice reduction and support facilitating perspective‐getting in conversations intended to reduce exclusionary attitudes.